Оцінка методів компонентного аналізу приросту середньої тривалості життя - Стефановський, А.І. (Інститут демографії та соціальних досліджень НАН України, 2006)
В статье дана оценка различным методам компонентного анализа приращения средней продолжительности жизни (Дж. Полларда, Е. Арриага, Е. Андреева, Ю. Корчака-Чепурковского). Разработано 2 критерия оценки. Показано, что выполнение критерия 1 является необходимым, а критерия 2 – достаточным условием верности предложенного автором статьи метода. Сделано обобщение формулы Ю. Корчака-Чепурковского для компонентного анализа. In clause the estimation is given to various methods of the component analysis of an increment of average life expectancy (JH. Pollard, E.Arriaga, E.Andreev, Y. Korchak-Chepurkovskiy). 2 criteria of an estimation are developed. It is shown, that performance of criterion 1 is necessary, and criterion 2 – a sufficient condition of method’s fidelity, offered by the author of clause. Generalisation of the Y. Korchak-Chepurkovskiy’s formula of the componental analysis is made.